DEMOKRASI DALAM PERSPEKTIF AL-QUR`AN - Ummu Sa’adah (Fakultas Syariah - IAI Al-Qolam Malang, 2021)
The substance of democracy is in line with the principles in the Qur'an, more precisely the Qur'an summarizes the concept of democracy with the keyword shura. The Qur'an views shura as the most important element for human life, both as individuals, members of society and political elites. In the shura system, it is necessary to consider taking sides with one party in the event of a disagreement. The party that must be supported in this case is the majority vote. Because the opinion of two people is closer to the truth than the opinion of one person even though the real truth is still in the hands of Allah SWT.